Radiochemical Separation of Nickel for 59Ni and 63Ni Activity Determination in Nuclear Waste Samples - Reis, Aluísio Sousa; Júnior; Temba, Eliane S. C.; Kastner, Geraldo F.; Monteiro, Roberto P. G. (IntechOpen, 2012)
None